Food beliefs and food supply chains: The impact of religion and religiosity in Israel. (February 2019) - Heiman, Amir; Gordon, Ben; Zilberman, David
Highlights: Religiosity affects food production & consumption leading specialized supply chains. Certification addresses consumer concerns of unobservable production technologies. Specialized chains serve high levels of religiosity; few large grocers serve lower. Demographic shifts, immigration of secular Jews increased diversity of supply chains. Abstract: This paper demonstrates that religion and religiosity affect norms, which affect food consumption patterns and production. Heterogeneity and asymmetric information lead to multiple certification channels as well as multiple supply chains. Major supply chains may address multiple constituencies that are secular or less religious. Technological change affects norms and thus the food system. We obtain these results by analyzing the food systems for meat products in Israel where there are three religions – Jews, Muslims, and Christians – and people assign themselves three levels of religiosity – secular, conservative, and orthodox. Israel has multiple Kosher and Halal certifiers and several specialized supermarket chains for orthodox groups. Its main supermarket chains serve secular and some conservative segments. The immigration of secular Jews from Russia led to the proliferation of non-Kosher supply chains and products, and increased consumption of pork. New technologies and higher incomes led to emergence of fast food chains serving orthodox Jews that had previously tended to eat at home.